2009
DOI: 10.1073/pnas.0907195106
|View full text |Cite
|
Sign up to set email alerts
|

Conformational selection or induced fit: A flux description of reaction mechanism

Abstract: The mechanism of ligand binding coupled to conformational changes in macromolecules has recently attracted considerable interest. The 2 limiting cases are the ''induced fit'' mechanism (binding first) or ''conformational selection'' (conformational change first). Described here are the criteria by which the sequence of events can be determined quantitatively. The relative importance of the 2 pathways is determined not by comparing rate constants (a common misconception) but instead by comparing the flux throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
661
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(692 citation statements)
references
References 51 publications
29
661
1
1
Order By: Relevance
“…Flux analyses have shown that ligand and protein concentrations are central in determining whether conformational selection or induced fit pathways dominate. It is in fact possible for a conformational selection model to dominate at low substrate concentrations but to be replaced by induced-fit binding at higher substrate concentrations, as was demonstrated to be the case for DHFR (Hammes et al 2009). A generic problem with the conformational selection model is that active states of enzymes may be unavailable to substrates due to steric occlusion (Sullivan & Holyoak, 2008).…”
Section: Detection Of Functional High-energy Protein Statesmentioning
confidence: 99%
“…Flux analyses have shown that ligand and protein concentrations are central in determining whether conformational selection or induced fit pathways dominate. It is in fact possible for a conformational selection model to dominate at low substrate concentrations but to be replaced by induced-fit binding at higher substrate concentrations, as was demonstrated to be the case for DHFR (Hammes et al 2009). A generic problem with the conformational selection model is that active states of enzymes may be unavailable to substrates due to steric occlusion (Sullivan & Holyoak, 2008).…”
Section: Detection Of Functional High-energy Protein Statesmentioning
confidence: 99%
“…3,38,40−45 The same mechanism was successfully borrowed for monomeric enzymes to explain substrate mediated conformational redistributions along the reaction coordinate. 2,5,25,46 Regulated enzymes, however, in addition to their reaction coordinate, have a conformational-regulatory coordinate. A major structural rearrangement has to occur for the enzyme to adopt the active conformational state, where the active site is accessible and catalysis may occur.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The opposite scenario, of rapid transitions between non-binding and binding conformations together with the ability to form binding contacts even in the unbound state, would tend to favour induced fit. [22][23][24] Experiments have yielded valuable results on many aspects of IDP structure and function. The most powerful methods are single molecule FRET experiments, which can provide information on the overall dimensions 25 and dynamics 26 of unbound IDPs, and NMR experiments which give more localised and higher resolution structural data 27,28 and also mechanistic insights.…”
Section: Introductionmentioning
confidence: 99%